Importance of New Edible Oil Extracted from Seeds of Seven Cereals Species - Amor Slama; Ammar Cherif; Sadok Boukhchina (Journal of Food Quality)
Cereals constitute a major source of human and animal nutrition. In spite of the extensive production of numerous cereal species, some information is unavailable in terms of lipid composition. Due to the oil increasing demand by the overgrowth of the world population, oleaginous species have encountered problems in recent years. In order to find new sources of edible oil, the aim of this study was to describe the importance of seventeen varieties oil of seven cereal species. Oils were extracted by the Soxhlet method, and fatty acids were measured by gas chromatography. The present study demonstrated that the lipid content of cereal seeds ranged from 1.42% to 5.97%. In average, oat, millet, and maize had significantly higher lipid content, respectively, 5.97%, 5.06%, and 4.71%. The main fatty acid recorded in the studied cereal species, except oat, was linoleic acid C18 : 2 (ω6). Regarding the essential fatty acids linoleic acid C18 : 2 and linolenic acid C18 : 3 (ω3), the oil of all studied species, except oat, was rich in ω6 fatty acids (47.50 to 60.13%) and poor in ω3 (0.45% to 5.33%). The content of unsaturated fatty acids in all studied species ranged from 77.22 to 81.89%. Cereal oil was considered as highly unsaturated oil with the presence of the essential fatty acids necessary for human health. Therefore, cereal oils could be commercialized in small quantities in pharmacies or parapharmacies.